The Relationship Between Depression and Anxiety Symptoms of Adult PWE and Caregivers in a Tertiary Center - João, Rafael Batista; Nogueira, Mateus Henrique; Morita-Sherman, Márcia Elisabete; Alvim, Marina Koutsodontis Machado; Johnny, Steven; Pereira, Haryton; Pinheiro, Hildete Prisco; Cendes, Fernando; Yasuda, Clarissa Lin (Frontiers in Neurology, 2022)
Background: Although several studies have emphasized the association between epilepsy and psychiatric disorders, fewer have investigated the impact of epilepsy on caregivers' emotional status, mainly in adult people with epilepsy (PWE). Here we investigated depressive symptoms, suicidal ideation, and anxiety symptoms in a large group of adult PWE and their caregivers. Methods: We analyzed symptoms of depression (with the Beck Depression Inventory-II [BDI-II]), suicidal ideation (with BDI-II item 9), and anxiety symptoms (with the Beck Anxiety Inventory) in a large group of adult PWE (N = 548 [60% women; median age 41]) and caregivers (N = 191 [72% women; median age 47]) from a Brazilian tertiary center, considering sociodemographic and clinical aspects. We also applied the Liverpool Adverse Events Profile to assess anti-seizure drugs adverse events. Results: While the presence (p = 0.026) (and intensity, p = 0.007) of depressive symptoms and suicidal ideation (p = 0.02) were higher in PWE compared to caregivers, the proportion of clinical anxiety symptoms (p = 0.32) (and the intensity, p = 0.13) was similar in both groups. Although the rates of suicidal ideation were higher in focal epilepsy (20%), both generalized genetic epilepsy and caregivers also presented elevated frequencies (11%) of suicidal ideation. The analyses of 120 patient-caregiver dyads revealed that the intensity of depressive symptoms in PWE (but not anxiety) correlated with the intensity of depressive (r = 0.35; p < 0.001) and anxiety (r = 0.25; p = 0.01) symptoms in their caregivers. In the multivariate analyses of PWE, focal epilepsy (compared to GGE) was associated with clinical depressive symptoms (OR 2.1) and suicidal ideation (OR 3.2), while recurrent seizures (compared to the seizure-free group) were associated with suicidal ideation (OR 2.6) and anxiety symptoms (OR 2.1). Also, caregivers with anxiety symptoms were 8 times more likely to exhibit depressive symptoms, and those with depressive symptoms were 8 times more likely to present anxiety symptoms. Conclusion: Our study suggests that specific attention for the caregivers’ mental health is as essential as PWE. There is an urgent need for more studies involving caregivers to identify their emotional distress and provide adequate treatment.